Tinjauan Sistematis tentang Mekanisme Antidiabetik Kombucha dalam Regulasi Kendali Glikemik - Rahaju Ningtyas, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The study used a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. A total of 18 scientific articles from 2013–2025 were selected from the Scopus database, consisting of eight in vitro studies, four in vivo studies, and one clinical trial. Data extracted included the type of fermentation substrate, microbial composition, fermentation duration, and biochemical parameters related to glucose regulation, antioxidants, SCFAs, and α-glucosidase/α-amylase enzyme inhibition. The synthesis results showed three main pathways of kombucha's antidiabetic activity: (1) increased antioxidant activity (SOD, GSH, catalase), (2) regulation of gut microbiota and increased SCFAs that improve insulin sensitivity, and (3) inhibition of carbohydrate digestive enzymes by up to 83%. Substrate variations and fermentation duration of 7–14 days affected the levels of polyphenols, organic acids, and flavonoids. Clinical studies showed a 30% reduction in fasting blood glucose levels after four weeks of kombucha consumption. Kombucha has been shown to work through a synergistic multi-pathway mechanism involving biochemical and microbial activity in lowering blood glucose levels. These findings strengthen kombucha's potential as a natural fermented nutraceutical agent for glycemic control. Further research is recommended to conduct long-term clinical trials and metabolomic analyses to more precisely map the microbial-bioactive-glycemic response relationship.